Maimun Superblock in Medan City With a Green Architecture Approach - Abdillah , Wahyu; Adha , Fathiyatul Mumtazah Al (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
Medan City is faced with urban development problems that result in increased mobility and population density. Urban expansion requires infrastructure development to facilitate economic activities concentrated in city centers. Medan as a major economic center is experiencing rapid growth, demanding adequate facilities for offices, transportation, education, and economic centers. This growth increases population density, reduces available land and increases housing demand. To address mobility, population density, and housing needs, a Mix-Use development model, specifically the Superblock concept that integrates residential, commercial, and recreational spaces with a green environmental perspective, is proposed. Superblok efficiently accommodates high density through vertical construction, emphasizing green architecture for the comfort and enjoyment of visitors, users, and staff. Research methods include case studies, hands-on research, and strategic analysis to determine functional needs, site location, and architectural principles that support specific concepts.